PENGARUH EKSPEKTASI RETURN DAN RISIKO INVESTASI TERHADAP MINAT INVESTASI MAHASISWA DI GALERI INVESTASI SYARIAH IAIN KERINCI (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2021)
This study was conducted with the intention of analyzing the effect of expected return and investment risk on student interest in investing in Islamic stocks at the Islamic Investment Gallery IAIN Kerinci. Therefore, as many as 59 students of IAIN Kerinci were taken as samples, where these students were students who had made investments. Data analysis was carried out using multiple linear regression, where the results showed that partially expected return had a positive and significant effect on student interest in investing in Islamic stocks at the Sharia Investment Gallery IAIN Kerinci, while investment risk had no significant effect. Simultaneously, the expected return and investment risk affect the interest of students to invest in Islamic stocks at the Sharia Investment Gallery of IAIN Kerinci, with the magnitude of the influence being 52.7%.